Military tax in Ukraine - Pogribna, Alexandra (My University, 2014)
The Ukrainian Tax System has developed radically since Ukrainian independence till present.
Keywords: military tax; reform; ibudget revenues; військовий податок; реформа; доходи бюджету; военный налог; доходы бюджета